Analysis of Influencing Factors Human Development Index of Central Java Province Using Exploratory Factor Analysis Method - Agustini Tripena; Esa Anugrah Salsabila (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
Indonesia occupies the fifth position of the country with the largest population in the world. The population sector in Indonesia must be a concern given the high population. The large population can be one of the factors that have a positive impact on advancing the country if the existing human resources are utilized as well as possible to increase development. One of the ways to maximize human development to advance the country's development can be done by analyzing what factors can affect the human development index. In this study, the factors affecting the human development index will be analyzed using the variables average length of schooling, expected length of schooling, life expectancy, average monthly expenditure on food, adjusted per capita expenditure, number of poor people, and the poverty line. poverty by using the Exploratory Factor Analysis method.